"To them, we're just kids from the hood": Citizen-based policing of youth of color, "white space, " and environmental gentrification. (December 2020) - Harris, Brandon; Rigolon, Alessandro; Fernandez, Mariela
Abstract: In gentrifying communities, youth of color are often the subject of citizen-based policing by white residents, who use nonemergency 311 calls to police unwanted behaviors, eliminate incumbent symbols of ownership (e.g., graffiti), and gain control of the space. To date, little research has examined such policing efforts in neighborhoods experiencing environmental gentrification. In these neighborhoods, parks and greenways are often established to attract white newcomers, and thus citizen-based policing to ensure that parks remain "white spaces" might be particularly strong. Using a mixed-method design, we examined the citizen-based policing of youth proximate to Chicago's 606, an urban greenway connected to environmental gentrification. Interviews revealed that white residents frequently and increasingly used citizen-based policing to monitor and control youth of color's behaviors on The 606. In response, youth avoided greenway segments in white-majority neighborhoods, used the greenway when less populated, or avoided it altogether. A mixed-effects quasi-Poisson model supported these findings, showing that the number of graffiti-related 311 calls significantly increased in the years preceding and following the greenway's opening, particularly in areas closest to The 606. Planners and policymakers need to recognize these issues and work to ensure park spaces in gentrifying areas promote inclusion and diversity. Highlights: Citizen-based policing creates "white space" in areas undergoing environmental gentrification. Citizen-based policing targets minority youth behaviors in parks in these areas. The number of graffiti-related 311 non-emergency calls increased with environmental gentrification. Minority youth may stop using urban parks due to citizen-based policing.